Experimental Study and Modelling of the Pyrolysis of Organic Dusts: Application to Dust Explosions - N. Cuervo; O. Dufaud; D. Torrado; N. Bardin-Monnier; L. Perrin; A. Laurent (Chemical Engineering Transactions, 2013)
Pyrolysis gases have been obtained by heating wheat starch thanks to a modified Godbert-Greenwald oven under argon atmosphere. The gases have been analyzed by micro-gas chromatography. The explosivity of both starch and pyrolysis gases have been compared. Totally different explosive behaviours have been observed for the gases and for pure dusts, which highlights the influence of the pyrolysis step on the explosivity of organic particles with diameters greater than 30 µm. However, tests carried out with pyrolysis gases and glass beads mixtures also demonstrate that the impacts of heat transfer and turbulence/combustion interactions should not be neglected. In addition, a one dimensional finite-volume scheme has been developed to represent the pyrolysis of a single starch particle. The model has been validated for particles exposed rapidly at high temperatures (1,000 K). The characteristic times of the pyrolysis have then been determined, which confirms the importance of the primary gasification of the particle in the rate-limiting step of the dust explosion. These results also provide a perspective for understanding the specific behaviour of gas/dust hybrid mixtures towards explosion.